Ground closure monitoring systems on trial in deep to ultra-deep mechanized gold mining - Zvarivadza, T.; Sengani, F. (CRC Press, 2022)
As mining progresses towards deep to ultra-deep levels, rockbursts, support failure, stope closure, and stress fracturing become more pronounced. Electronic monitoring cable anchor devices, extensometers, closure meters, strain cells and FOG lights are currently employed in deep to ultra—deep level mechanized gold mining in South Africa for stability monitoring. The main objective of the study was to monitor the impact of blasting longhole stopes within development cuts on ground deformation or ground closure. This is meant to improve safety of employees that connect from one point to another performing different duties in the mine. This was achieved through installation of ground closure monitoring systems that measure the strain or ground deformation as mining progresses. However, the monitoring systems were performing differently based on their effectiveness. It was found that both electronic monitoring cable anchors and extensometers were more sensitive as compared to FOG lights through detecting micro strain or deformation. Numerical modelling was also conducted to determine the rate of ground closure influenced by blasting longhole stopes within development cuts. The model indicated that the ground closure rate ranged from 400 mm to 600 mm. The electronic Monitoring cable anchors were only installed along the ramp and haulages, strain measurements were found to range from −1 × 10−7 to 1.5 × 10−7. The extensometers were installed within development ends where longhole stopes were blasted, the closure was found to range from 200 mm to 500 mm. It was noted that rapid blasting of longhole stopes within development cuts led to rapid ground closure and rockmass instability as well as massive Falls of Ground.